LAMP proteins account for the maturation delay during the establishment of the Coxiella burnetii-containing vacuole - Schulze-Luehrmann, Jan; Eckart, Rita A.; Oelke, Martha; Saftig, Paul; Liebler-Tenorio, Elisabeth; Lührmann, Anja (Cellular Microbiology, 2016)
The obligate intracellular pathogen Coxiella burnetii replicates in a large phagolysosomal-like vacuole. Currently, both host and bacterial factors required for creating this replicative parasitophorous C. burnetii-containing vacuole (PV) are poorly defined. Here, we assessed the contributions of the most abundant proteins of the lysosomal membrane, LAMP-1 and LAMP-2, to the establishment and maintenance of the PV. Whereas these proteins were not critical for uptake of C. burnetii, they influenced the intracellular replication of C. burnetii. In LAMP-1/2 double-deficient fibroblasts as well as in LAMP-1/2 knock-down cells, C. burnetii establishes a significantly smaller, yet faster maturing vacuole, which harboured more bacteria. The accelerated maturation of PVs in LAMP double-deficient fibroblasts, which was partially or fully reversed by ectopic expression of LAMP-1 or LAMP-2, respectively, was characterized by an increased fusion rate with endosomes, lysosomes and bead-containing phagosomes, but not by different fusion kinetics with autophagy vesicles. These findings establish that LAMP proteins are critical for the maturation delay of PVs. Unexpectedly, neither the creation of the spacious vacuole nor the delay in maturation was found to be prerequisites for the intracellular replication of C. burnetii.
EVALuna2:7697